2016
DOI: 10.1177/0142723716648845
|View full text |Cite
|
Sign up to set email alerts
|

Metaphor, metonymy, and their interaction in the production of semantic approximations by monolingual children: A corpus analysis

Abstract: The present study looks into the largely unexplored territory of the cognitive underpinnings of semantic approximations in child language. The analysis of a corpus of 233 semantic approximations produced by 101 monolingual French-speaking children from 1;8 to 4;2 years of age leads to a classification of a significant number of them as instances of a set of principle-governed cognitive operations, including metaphor and metonymy-based cognitive operations, and conceptual complexes, such as metaphtonymies and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
(78 reference statements)
1
6
0
1
Order By: Relevance
“…This corresponds with studies done by Péréz-Hernández and Duvignau (2016) on French speaking children and Rundblad and Annaz (2010) on English children in which it was found that metonymy is more basic than metaphor.…”
Section: Made When the Conceptualisation Process Needs More Descriptisupporting
confidence: 90%
“…This corresponds with studies done by Péréz-Hernández and Duvignau (2016) on French speaking children and Rundblad and Annaz (2010) on English children in which it was found that metonymy is more basic than metaphor.…”
Section: Made When the Conceptualisation Process Needs More Descriptisupporting
confidence: 90%
“…Although some claim that metaphor competence develops within a continuum, the current study, as well as other recent studies (e.g., Willinger et al, 2017), indicates that children and adolescents might show spurts in metaphorical language development. Regarding the development of metaphor processing, it was shown that (very) young children also understand some metaphors (e.g., Gibbs & Colston, 2012;Pérez-Hernández & Duvignau, 2016). Research indicates that, before effectively using explicit techniques like COMPARISON and CATEGORIZATION that are commonly associated with metaphoric language (Gentner & Bowdle, 2008;Glucksberg, 2001), pragmatic conventions are constructed long before actual language in terms of metaphorical thought (e.g., Alessandroni, 2017).…”
Section: Development Of Metaphor Identification and Comprehension: Chmentioning
confidence: 99%
“…Research indicates that, before effectively using explicit techniques like COMPARISON and CATEGORIZATION that are commonly associated with metaphoric language (Gentner & Bowdle, 2008;Glucksberg, 2001), pragmatic conventions are constructed long before actual language in terms of metaphorical thought (e.g., Alessandroni, 2017). In the course of development, children start very early to overextend the meanings of words in order to label things or express (mostly) non-abstract concepts for which they lack literal terms (see, e.g., Clark, 2003;Pérez-Hernández & Duvignau, 2016;Pouscoulous, 2011). Until approximately age four, children use metaphors in the form of overextended meanings of terms already acquired (Nerlich, Clarke, & Todd, 1999), whereas at some point they are able to deliberately extend meanings in order to intentionally overcome literal borders (e.g., Pouscoulous, 2011).…”
Section: Development Of Metaphor Identification and Comprehension: Chmentioning
confidence: 99%
“…Children's performance in this area improves by the age of 5, at which time they can produce similarity-based explanations when asked about expressions that involve comparisons between objects (Vosniadou 1987;Özçalişkan 200;Siltanen, 2009). Th us, preschool children can both understand and spontaneously produce a variety of expressions based on similarity, an achievement that is considered to be the earliest form of metaphorical ability in young children (Pérez-Hernández, Duvignau, 2016). Children of any age have no diffi culty understanding feature-based commonalities between objects, but it is only with increasing age that they can begin to understand mappings based on relational structure, and accordingly, produce explanations that refl ect this understanding (Özçalişkan, 2007).…”
Section: The Age Of the Participantsmentioning
confidence: 99%